Production of high quality bio-oil via pyrolysis of lignocellulosic biomass: a review on role of plastic and catalyst types / Siti Maryam Wasli and Hamizura Hassan - Wasli, Siti Maryam; Hassan, Hamizura (2021)
Biomass is one of the alternatives and sustainable source of energy that exists in abundant, renewable and widely available, as well as emits particularly low CO2 content. It can be used to produce biofuels via the pyrolysis process, which is an environmentally safe way of employing biomass and solid wastes. Moreover, co-pyrolysis of biomass and plastic produced significant positive effect, as the bio-oil obtained has high calorific value close to conventional fuel. By utilizing the biomass and plastic waste as co-reactants help to reduce the fuel consumption and alleviate the environmental pollution. However, elimination of oxygenated compounds poses a considerable challenge. Catalytic co-pyrolysis is utilized to enhance the quality of biofuel produced from co-pyrolysis of biomass and plastic. The catalytic co-pyrolysis process involved two materials as feedstock and an acidic catalyst for production of biofuel. This technique promotes the production of high-quality bio-oil through acid catalyzed reduction of oxygenated compounds and mutagenic polyaromatic hydrocarbons. This paper review on the role of plastic and catalyst types for the production of high-quality bio-oil via pyrolysis of lignocellulosic biomass. This review focuses on the potential of plastic such as HDPE, LDPE, PET, PC, PVC and PS as co-feed in co-pyrolysis to produce valuable liquid fuel. Also, to study the types of zeolite-based catalyst to further improve the process and the quality of biofuels in catalytic copyrolysis of biomass and plastic.